Integration of Cooperation among Network Partners in Driving the Policy of Human Development throughout the Life of Early Childhood Group, Phichit Province, Thailand - Chinnawut, Siriluk; Sirisunhirun, Somboon; Amornsiriphong, Somsak; Ploywan, Phut; Rugchatjaroen, Krish (Journal of Ecohumanism, 2025)
Background: In developing early childhood children potential, it was not only helps creating a solid foundation for the individual growth, but also a worthwhile investment that provide the highest social returns in the long run. Objective: This research aimed at studying the roles and factors affecting the success of the implementation of the lifelong human development policy for early childhood children of the network in Phichit Province, as well as proposing a model of network partner participation in implementing the lifelong human development policy in Phichit Province. Results: The study results showed that early childhood development in Phichit Province still faced problems in physical and intellectual development, which indicated about the need for integrated actions in many dimensions. Key factors affecting the policy success included 1) clear and concrete policy content, 2) cooperation between the government and the community, 3) participation of local people, and 4) management under effective leadership. Concerning the participation model of the Pichit model network, it focused on the policies adjusting policies to be in line with the local area and creating cooperation from all sectors to support early childhood development effectively, covering the awareness campaign to monitoring and evaluation. Conclusion: The "Phichit Model" was an example of an integrated guideline to human resource development throughout the life which was in line with the 20-year National Strategic Plan. The sustainability of early childhood development required collaboration from all sectors to be able to adapt and acted effectively and responded to the needs of diverse areas.